Du « je » au « nous ». Le Théâtre de l'opprimé comme grammaire d'une parole collective - Sophie Coudray
The Theatre of the Oppressed appears as a theatrical pedagogy dedicated to "non-actors" - oppressed, vulnerable subjects - whose openly activist purpose implies the construction of a collective political subject. Its method allows an overtaking of the individual narrative in order to work towards a pooling, which is essential for critical reflection and the development of a political discourse that anyone can carry on stage on behalf of everyone. This paper aims at exploring Augusto Boal's approach and the operation of his theatrical pedagogy. The functioning of Theatre of the Oppressed's grammar will be analyzed and the stages of the political subject construction identified, while taking account of the singularity of theatrical language. In doing so, I will also question how the fact that Theatre of the Oppressed has become bound to citizenship education troubles the very definition of the political subject, highlighting the contradictions of this theatrical grammar and its uses.